Psychosomatic status and myocardial hypertrophy remodelling specificity - G. A. Usenko; A. G. Usenko; D. V. Vasendin; O. V. Nischeta (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Special antihypertensive therapy was combined with a prelimenary (6 months) and more pronouced approach of the left ventricle myocardial mass and of the left ventricule index as well as of the systolic and diastolic functions to those in healthy people of the corresponding temperament and anxiety.